1996
DOI: 10.1111/j.1528-1157.1996.tb00539.x
|View full text |Cite
|
Sign up to set email alerts
|

Postictal Alteration of Sodium Content and Apparent Diffusion Coefficient in Epileptic Rat Brain Induced by Kainic Acid

Abstract: The increase in MR visible sodium, associated with the decrease in ADC is consistent with the hypothesis that sequential seizures caused an increase in sodium influx and perturbation of membrane ion homeostasis, which eventually evolved into an irreversible phase of cellular edema, with increased MR visible intracellular sodium and decreased ADC. Return of ADC to near-control level and persistent high sodium level at 7 days may be explained by the increase in extracellular space and tissue necrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
71
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(75 citation statements)
references
References 19 publications
1
71
1
Order By: Relevance
“…By using the experimental model of kainic acidinduced status epilepticus in rats, it has been shown that postictal ADC was decreased in the piriform cortex, hippocampus, and amygdala for 24-72 h and normalized within 9 days (7,8). The ADC changes were closely correlated with the presumed area of seizure onset and the resulting histopathologic changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By using the experimental model of kainic acidinduced status epilepticus in rats, it has been shown that postictal ADC was decreased in the piriform cortex, hippocampus, and amygdala for 24-72 h and normalized within 9 days (7,8). The ADC changes were closely correlated with the presumed area of seizure onset and the resulting histopathologic changes.…”
Section: Discussionmentioning
confidence: 99%
“…DWI has demonstrated great utility for the early identification of cerebral ischemia both in animal models (3) and in humans (43). Data from animal models of focal seizures (6)(7)(8)(9)(10) and from a case report on one patient during status epilepticus (1 l) suggest that DWI may be a sensitive tool for the localization of active epileptogenic foci. In this study, we report on the correlation between electrocorticographic (ECoC) seizure activity and focal DWI changes in a patient with left focal motor status epilepticus.…”
mentioning
confidence: 99%
“…In recording ictal SPECTs, the interictal SPECT is helpful in determining the extent of blood flow changes between the two conditions (83). Recent data from animal models and case reports on patients suggest that diffusionweighted magnetic resonance imaging (DWI) may be an additional noninvasive technique for localization of the epileptogenic zone (84)(85)(86)(87), and preliminary data suggest that it may be particularly helpful in patients with lesional epilepsy (88). Surface EEG is characterized by a higher incidence of interictal spikes compared to HS (89).…”
Section: General Considerationsmentioning
confidence: 99%
“…On brain MRI, the cerebral cortical T2 hyperintensity with diffusion restriction is commonly observed in patients with seizure, and these findings were usually accompanied by focal parenchymal swelling and increased vascularity (4,11,12). The seizure-induced cellular disturbance occurs due to various phenomena, such as vasogenic and cytotoxic edema, increased permeability, loss of autoregulation, regional ischemia, and excitotoxicity (13,14). These changes usually result in an increase of T2 and FLAIR signal intensity, and variable alterations on DWI and ADC (15,16).…”
Section: Discussionmentioning
confidence: 99%